Autophagy induction by sera from women undergoing an in vitro fertilization cycle varies with subsequent outcome. (September 2016) - Sisti, Giovanni; Kanninen, Tomi T.; Di Tommaso, Mariarosaria; Witkin, Steven S.; Spandorfer, Steven D.
Highlights: Autophagy induction by patients' sera varies according to the IVF outcome. Deficiency in autophagy induction are related to pregnancy loss. Excessive autophagy induction is related to ectopic pregnancy. Abstract: Autophagy maintains intracellular homeostasis during placental development and embryogenesis. We evaluated if differences in the autophagy-inducing capacity of sera from women undergoing an in vitro fertilization (IVF) cycle predicted subsequent pregnancy outcome. In this retrospective study, sera collected from 94 women at the time of intrauterine embryo implantation were incubated with peripheral blood mononuclear cells (PBMCs) from healthy donors. The PBMCs were lysed and autophagy induction measured by determination of the p62 concentration. A reduced capacity for autophagy induction was associated with defective implantation while an elevated level of autophagy was associated with ectopic pregnancy.